Principles of macroeconomics - Stiglitz, Joseph E. (W. W. Norton, 1997)
This book is divided into five parts: Introduction; Full-Emplooyment Macroeconomics; Unemployment Macroeconomics; Dynamics and Macro Policy; and Issues in Macroeconomic Policy.